Teachers’ Job Performance and School Effectiveness in Public Senior Secondary Schools in Oyo State, Nigeria - Olabisi Aminat Owonwami; Oluwakemi Olabisi Akinnubi; Jamiu Olatunji Ottan; Abdullahi Ayinla Olokoba; Abubakar Adeleke Towobola (Eduvis : Jurnal Manajemen Pendidikan Islam, 2025)
The persistent underperformance of schools in Oyo State, Nigeria, has raised critical concerns about the effectiveness of teachers, whose roles are central to educational quality. This study investigated the impact of teachers’ job performance on school effectiveness in public senior secondary schools in the state. The objective was to examine how specific dimensions of job performance—lesson plan preparation, teaching methods, use of instructional materials, and record keeping—relate to school effectiveness. The study employed a descriptive survey design of a correlational type. From a population of 11,430 teachers across 563 schools, a stratified random sample of 387 teachers was drawn. Data were gathered using a validated "Teachers' Job Performance and School Effectiveness Questionnaire" (TJPSEQ). At the significance level of 0.05, descriptive statistics (mean and standard deviation) and Pearson Product-Moment Correlation were utilized in the study. Findings revealed moderate teacher job performance (M=2.79) and school effectiveness (M=2.16). Statistically significant relationships were found between overall job performance and school effectiveness (r=0.810, p<0.05), as well as with individual indicators such as lesson planning (r=0.718), teaching methods (r=0.980), instructional materials (r=0.657), and record keeping (r=0.775). The study concluded that teachers’ performance strongly determines school effectiveness. It contributes to knowledge by highlighting key performance domains directly influencing educational outcomes. The study recommends targeted professional development, resource allocation, and structured evaluation systems to enhance teacher performance and regional school effectiveness.